Preparation of Alpinia galanga stem based activated carbon via single-step microwave irradiation for cationic dye removal - N.A. Ahammad,; M.F.M. Yusop,; A.T. Mohd Din,; M.A. Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The focal point of this study is to synthesis Alpinia galanga Stem-based activated carbon (AGSAC) by using single-step microwave irradiation and testing it for the removal of cationic dye, methylene blue (MB) from aqueous solution. AGSAC was prepared under the flow of carbon dioxide (CO2) for the gasification effect. The factors of contact time (from 0 to 24 h) and initial concentration (25-300 mg/L) on the adsorption performance of AGSAC were studied. With the aid of response surface methodology (RSM) via face-centered composite design (FCD), optimum preparation conditions for AGSAC were found to be 400 W for radiation power and 4 min for activation time, respectively, which resulted in 95.67% of MB dye removal. The optimized AGSAC has a Bruneaur-Emmet-Teller (BET) surface area of 172.19 m2/g, mesopore surface area of 103.32 m2/g, a total pore volume of 0.1077 cm3/g, and fixed carbon content of 47.63%. The pore diameter of AGSAC was found to be a mesoporous type with a pore diameter of 2.50 nm. Freundlich isotherm and pseudo-second-order were found as the best-fitted model for MB adsorption equilibrium and kinetic respectively onto prepared AGSAC. Intraparticle diffusion was found to be the rate-limiting step.